2022
DOI: 10.18502/ajmb.v14i2.8886
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Multi-Epitope Antigen for Serodiagnosis of Strongyloides stercoralis Based on L3Nie.01 and IgG Immunoreactive Epitopes

Abstract: Background: Serological diagnosis of Strongyloides stercoralis  (S. stercoralis) is frequently challenging because of cross-reactivity with other parasitic nematodes. Therefore, it is necessary to introduce novel serological tests with high performance to properly diagnose this neglected parasitic infection. The purpose of the current study was to design a multi-epitope construct for the diagnosis of S. stercoralis. Methods: For the purpose of this study, first, highly antigenic segments and potential im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Diagnosis: Omics approaches were used for discovering a unique antigen specific for diagnosis of S. stercoralis either in serum [55] or stool samples [56] . In the first study, the investigators designed a multi-epitope antigen based on L3Nie.01 and IgG immunoreactive epitopes [55] .…”
Section: Strongyloides Stercoralismentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnosis: Omics approaches were used for discovering a unique antigen specific for diagnosis of S. stercoralis either in serum [55] or stool samples [56] . In the first study, the investigators designed a multi-epitope antigen based on L3Nie.01 and IgG immunoreactive epitopes [55] .…”
Section: Strongyloides Stercoralismentioning
confidence: 99%
“…Diagnosis: Omics approaches were used for discovering a unique antigen specific for diagnosis of S. stercoralis either in serum [55] or stool samples [56] . In the first study, the investigators designed a multi-epitope antigen based on L3Nie.01 and IgG immunoreactive epitopes [55] . Utilizing phylogenetic comparison, the second study identified five specific coproantigens for diagnosis in stool samples, SCP/TAPS proteins family, transthyretin-like, AChE, aspartic peptidase, and prolyl oligopeptidase [56] .…”
Section: Strongyloides Stercoralismentioning
confidence: 99%